2009
DOI: 10.1515/iral.2009.016
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating cognitive complexity across task types and its impact on learners' interaction during oral performance

Abstract: The goal of this study is to investigate the impact of manipulating the cognitive complexity of three different types of oral tasks on interaction. The study first considers the concepts of task complexity and interaction and then examines the specific studies that have looked at the effects of increasing task complexity on conversational interaction. In the experiment, learners of English as a foreign language organized into 27 dyads carry out three different types of tasks: a narrative reconstruction task, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(91 citation statements)
references
References 38 publications
5
82
2
2
Order By: Relevance
“…To provide a more specific definition, some scholars (e.g., Gilabert et al, 2009;Robinson, 2001) described task complexity as the level of variability that any particular learner experiences while performing different tasks. There are, however, other scholars (e.g., Ellis, 2003) who confined the scope of task complexity to a particular task's degree of difficulty.…”
Section: Cognitive Complexity Levels In Writingmentioning
confidence: 99%
“…To provide a more specific definition, some scholars (e.g., Gilabert et al, 2009;Robinson, 2001) described task complexity as the level of variability that any particular learner experiences while performing different tasks. There are, however, other scholars (e.g., Ellis, 2003) who confined the scope of task complexity to a particular task's degree of difficulty.…”
Section: Cognitive Complexity Levels In Writingmentioning
confidence: 99%
“…In their study, Gilabert et al (2009) investigated the effects of +/-few elements and +/-no reasoning demand on learners' interaction. Sixty learners of English as a foreign language participated in the study.…”
Section: International Journal Of Linguisticsmentioning
confidence: 99%
“…Gilabert (2007) analyzed the effects of cognitive demands on accuracy and self-repairs as measures of learners' attention to form. In addition, Gilabert, Raron, and Llanes (2009) investigated the impact of cognitive demands on learners' oral interaction, focusing on interactional moves (i.e., negotiation of meaning, recasts, language-related episodes, and selfrepairs). Both studies concluded that increasing cognitive demands along the resource-directing variable generate more attention to form, even though there were slight differences in each task type.…”
Section: Robinson's Multiple-resource Modelmentioning
confidence: 99%
“…Second, as previously mentioned, Gilabert et al (2009) explored the nature of attention to form through interactional moves. In usual task engagement, however, negotiations are triggered by communication breakdown.…”
Section: Gaps In the Study Of Attention Orientation In L2 Oral Producmentioning
confidence: 99%